MODEL PENGELOLAAN WAKAF PENDIDIKAN BERBASIS BLOCKCHAIN: MENDUKUNG SDGS DI ERA SOCIETY 5.0 - Sepgiono, Sepgiono; Husnul Khatimah,; Hardiansyah, Hardiansyah (Juremi: Jurnal Riset Ekonomi, 2025)
This study explores the model of educational waqf management based on blockchain in Indonesia and its impact on achieving the Sustainable Development Goals (SDGs), particularly in education (SDG 4). Blockchain can enhance transparency, accountability, and efficiency in waqf fund management through the use of smart contracts that ensure funds are used according to their intended purpose. However, the implementation of this technology faces key challenges, such as low digital literacy and inadequate technological infrastructure in some regions. This study also highlights the crucial role of the government and Islamic financial institutions in supporting blockchain adoption for waqf management. With clear regulations and proper training, blockchain-based waqf can become an effective tool for more equitable educational development. The implications of this study emphasize the need for enhanced digital literacy, strengthened technological infrastructure, and the development of supportive regulations.